Analisis Laporan Ikhtisar Realisasi Anggaran Atas Pencapaian Kinerja Keuangan pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja Kota Mojokerto Periode 2020 - 2023 - Rohmatul Virnanda Aprilliani; Nur Ainiyah; Nurdiana Fitri Isnaini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is motivated by the increase and decrease in Original Regional Income at the One Stop Integrated Services Investment and Labor Service of Mojokerto City for the 2020 - 2023 period. The aim of this research is to find out how financial performance is measured by financial ratios. This type of research uses descriptive quantitative using secondary data in the form of budget realization reports for the One Stop Integrated Services Investment and Labor Service of Mojokerto City. This data analysis technique uses Financial Ratios. The results of the analysis show that there are fluctuations in performance which are influenced by various factors, including the COVID-19 pandemic which caused a decrease in investment and budget realization in 2020 and 2021. However, there was a recovery in 2022 with an increase in budget realization of up to 119%, reflecting the post-economic revival -pandemic. In 2023, the focus shifts to strengthening and sustaining economic recovery, with satisfactory performance results in several indicators, such as increasing the realized value of capital investment and the number of investors. However, there is a significant decline in the effectiveness ratio in 2023, indicating challenges in achieving budget targets. Overall, this research highlights the importance of adaptive strategies and strengthening institutional capacity to deal with changing economic dynamics, as well as the need for more effective policies to achieve long-term goals.